Sideband pump-probe technique resolves nonlinear modulation response of PbS/CdS quantum dots on a silicon nitride waveguide - Mirco Kolarczik; Christian Ulbrich; Pieter Geiregat; Yunpeng Zhu; Laxmi Kishore Sagar; Akshay Singh; Bastian Herzog; Alexander W. Achtstein; Xiaoqin Li; Dries van Thourhout; Zeger Hens; Nina Owschimikow; et al. (APL Photonics, 2018)
For possible applications of colloidal nanocrystals in optoelectronics and nanophotonics, it is of high interest to study their response at low excitation intensity with high repetition rates, as switching energies in the pJ/bit to sub-pJ/bit range are targeted. We develop a sensitive pump-probe method to study the carrier dynamics in colloidal PbS/CdS quantum dots deposited on a silicon nitride waveguide after excitation by laser pulses with an average energy of few pJ/pulse. We combine an amplitude modulation of the pump pulse with phase-sensitive heterodyne detection. This approach permits to use co-linearly propagating co-polarized pulses. The method allows resolving transmission changes of the order of 10−5 and phase changes of arcseconds. We find a modulation on a sub-nanosecond time scale caused by Auger processes and biexciton decay in the quantum dots. With ground state lifetimes exceeding 1 μs, these processes become important for possible realizations of opto-electronic switching and modulation based on colloidal quantum dots emitting in the telecommunication wavelength regime.